Cars and trucks - Holub, Joan; Holub, Joan; Regan, Dana (Penworthy, 2002)
With instruction for drawing race cars and school buses, budding artists can follow along to create their own pictures. Full color
Keywords: Cars -- Fiction; Trucks -- Fiction; Drawing Techniques -- Fiction